RiceAdvice: an android based decision support tools for Nigeria - CGIAR Research Program on Rice (2021)
Together with NARES, development organizations, and farmers’ groups, up to 2021 dry season, in total more than 96,000 recommendations were generated using RiceAdvice in Nigeria. Impact assessment was conducted in northern Nigeria.